A one-pot synthesis of biodiesel from leather tanning waste using supercritical ethanol: Process optimization. (November 2020) - Yuliana, Maria; Santoso, Shella Permatasari; Soetaredjo, Felycia Edi; Ismadji, Suryadi; Ayucitra, Aning; Angkawijaya, Artik Elisa; Ju, Yi-Hsu; Tran-Nguyen, Phuong Lan
Abstract: Due to its substantial lipid content, leather tanning waste (LTW) is regarded as a potential feedstock for the waste-derived biodiesel. To promote the valorization of LTW, one-pot synthesis of biodiesel via supercritical ethanol method was investigated. The influence of the three independent reaction variables, namely reaction time t (10, 20, 30, 40, 50 min), temperature T (300, 350, 400 °C) and ethanol to LTW molar ratio r eo (35, 40, 45), on the yield of fatty acid ethyl ester (FAEE) Y F was studied. The multilevel factorial design combined with the response surface methodology and three-way analysis of variance was employed to design and optimize the experiment in regards to the three independent variables. Based on the optimization results, the highest FAEE yield was predicted at 99.68% when t = 47.4 min, T = 374.6 °C, and r eo = 40.02. The actual FAEE yield was experimentally obtained at 98.91 ± 0.31% using the optimized reaction conditions. A deviation of 0.77% in the experimental verification shows a satisfactory agreement between the actual and predicted Y F . All reaction variables were also found to give a significant effect on the yield of FAEE. Graphical abstract: Image 1 Highlights: Tannery waste has been successfully converted to FAEE via supercritical ethanol. The optimum FAEE yield was obtained at 98.91 ± 0.31%, with a purity of 97.55%. The optimum operating condition is at t = 47.4 min, T = 374.6 °C, r eo = 40.02 The fuel properties of leather tanning waste-based FAEE conform to ASTM D6751 .